12 Observations by transoesophageal echocardiography post-watchman implantation in atrial fibrillation: a cause for concern?. (5th October 2017) - Traynor, B; Voon, V; McInerney, A; Hussein, H; Foley, D; McAdam, BF
Abstract : Introduction: Data regarding incidence of para-device leaks, persistent inter-atrial septal (IAS) defects and thrombus post-Watchman device implantation for atrial fibrillation is limited. We aimed to observe the incidence of para-device leaks, persistent IAS defects and thrombus detected by transoesophageal echocardiography (TOE), post-Watchman implantation. Methods: We retrospectively identified all patients (n=112) who had a Watchman device implanted between 2014–2016 at 2 Beaumont Hospital and Mater Private Hospital by a single operator. Within this cohort, patients who had undergone post-procedural TOE were analyzed for evidence of para-device leaks, IAS defects (including patent foramen ovale (PFO)) and thrombus. Mean LA pressure was at least 12 mmHg for all patients to ensure volume loading for adequate sizing. Data were expressed as mean ± SD and %. Results: Baseline demographic of all patients were age, 77 ± 7 years; male, 71%; CHADSVASC2 score, 4.3 ± 1.4; with left ventricular ejection fraction 51 ± 8%. All patients had a 14 F catheter across the inter-atrial septum to facilitate Watchman device delivery with mean size 26.8 ± 3.5 mm. Post-procedurally, 84% were on dual antiplatelet therapy and 16% were anti-coagulated for minimum duration of 8.6 ± 4.5 and 8.8 ± 4.3 weeks, respectively. 67% (n=75) had post-procedural TOE performed with duration from time of implant of 5.3 ± 4.2 months. Within this group, there was a 32% (n=24) incidence of para-device leaks post-Watchman implant. Size of leaks measured <2 mm (17%, n=13), 2–5 mm (13%, n=10), 5–10 mm (1%, n=1). Locations of para-device leaks identified were inferior (11%, n=8), superior (15%, n=11), non-specific (7%, n=5). In addition, one patient had device thrombus. Incidence of PFO pre-Watchman was 16%. There was a 17% (n=8) incidence of de novo IAS defects post-Watchman implant after comparison with pre-procedural TOE. Mean IAS defect size pre- and post-Watchman was 0.12 ± 0.38 vs 0.29 ± 0.58 cm, respectively. This change in IAS defect size of 0.13 ± 0.57 trended towards significance (p=0.09). Conclusions: A modest incidence of para-device leaks and rare but significant incidence of para-device thrombus was observed by TOE post-Watchman implantation. Further work is required to correlate potential implications of these findings on longer term outcomes related to recurrent strokes. The significance of persistent IAS defects post device implant also requires further investigation in longitudinal registry follow-up.